(untitled) (Iter, 2022)
Abanando Roapresents us a lucid essay about Leopardian influence on Clarence Finlayson, a Chilean philosopherfrom the first halfofthe XX century; in love with the poetry he regarded as “reflective experience ofpoetizing ”. In spite ofdifferences - Finlayson, opposed to Leopardi, was afervent believer- both menfelt that poetry and philosophy are “extremes which are dealt with in the same contení”. Finlayson sensed in Leopardi “a denial of onthologic nature which, though a negative way; can lead to a new perception o f being ” and maintained that his pesimism wasn ’t but “nostalgia o f the revelation of being itself Roa concludes that Finalyson and Leopardi “sought the same, although in opposite ways they were both “pilgrims of the absolute ”.